EMERGENCIES IN CORONAVIRUS DISEASE CAUSED BY COVID-19 VIRUS - Stanoeva, Jovana; Kisman, Aleksandar; Stojkovska, Snezana; Janevska, Vesna (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
In 2019, the new coronavirus was identified as the cause of a disease originating from the city of Wuhan in China, now known as SARS-CoV-2. The World Health Organization declared COVID-19 a pandemic in March 2020. Some people may have only a few symptoms or may not have any symptoms at all. Some people may experience worsening symptoms, such as shortness of breath and pneumonia, about a week after the onset of symptoms, and some may experience systemic complications caused by COVID-19 infection. Many of these complications can be caused by a condition known as cytokine release syndrome or cytokine storm. Cytokines can significantly damage vital organ tissue, including the lungs, heart, and kidneys. The pathology of coronavirus disease (COVID-19) is exacerbated by the progression of thrombosis, disseminated intravascular coagulation (DIC), and cytokine storm. Signs and symptoms of an emergency may include: difficulty breathing, rapid, shallow breathing, persistent chest pain or pressure, somnolence, confusion, collapse, pale, gray or blue skin, lips or nails - depending on skin tone. In hospitalized patients, constant monitoring and monitoring of parameters that may indicate a certain complication in the disease requiring prompt timely treatment, is necessary. The following emergency conditions, complications in COVID-19 have been described in this paper: acute respiratory failure, ARDS, COVID-19 coagulopathy and DIC, septic shock, rhabdomyolysis, acute renal failure, acute hepatic failure, acute heart disease, myocarditis, MIS-C, emergency neurological diseases and spontaneous rectus sheath hematoma. Keywords: emergencies in COVID-19, cytokine storm, COVID-19 coagulopathy, COVID-19 complications, multisystem inflammatory syndrome in children, MIS-C. https://doi.org/10.55302/JMS2143064s